The basal ganglia and thalamus of the long-tailed macaque in stereotaxic coordinates. A template atlas based on coronal, sagittal and horizontal brain sections - Lanciego, José L. (Springer-Verlag, 2011)
A stereotaxic brain atlas of the basal ganglia and thalamus of Macaca fascicularis presented here is designed with a surgical perspective. In this regard, all coordinates have been referenced to a line linking the anterior and posterior commissures (ac–pc line) and considering the center of the ac at the midline as the origin of the bicommissural space. The atlas comprises of 43 different plates (19 coronal levels, 10 sagittal levels and 14 horizontal levels). In addition to ‘classical’ cyto- and chemoarchitectural techniques such as the Nissl method and the acetylcholinesterase stain, several immunohistochemical stains have been performed in adjacent sections, including the detection of tyrosine hydroxylase, enkephalin, neurofilaments, parvalbumin and calbindin. In comparison to other existing stereotaxic atlases for M. fasicularis, this atlas has two main advantages: firstly, brain cartography is based on a wide variety of cyto- and chemoarchitectural stains carried out on adjacent sections, therefore enabling accurate segmentation. Secondly and most importantly, sagittal and horizontal planes are included. Sagittal planes are very useful for calculating oblique trajectories, whereas, clinical researchers engaged in neuroimaging studies will be more familiar with horizontal sections, as they use horizontal (also called “axial”) brain images in their daily routine of their clinical practices.